Collagenase Clostridium Histolyticum for the Treatment of Cellulite in the Buttocks and Thigh: Early Insights From Clinical Practice. (29th June 2022) - Graivier, Miles; Hill, David; Katz, Bruce; Boehm, Kristin A; Fisher, Juliya; Battista, China
Abstract: Background: Collagenase Clostridium histolyticum (CCH-aaes; QWO [Endo Aesthetics, Malvern, PA]) is an injectable, enzyme-based treatment indicated for treatment of moderate to severe cellulite on the buttocks of adult women. The minimally invasive nature of the treatment makes it an attractive option for targeted disruption of the fibrous septae which give rise to the dimples characteristic of cellulite in buttocks and thighs. Objectives: The article provides an overview of cellulite treatment with CCH-aaes, including patient identification and education, treatment planning, CCH-aaes dilution, injection technique, safety, and early experience with mitigation of adverse events, including bruising. Methods: As part of a continuing medical education (CME; xMedica, Alpharetta, GA) event on developments in cellulite treatment, a panel of experts developed a course and roundtable, which included lectures on cellulite physiology, new developments in the field of cellulite treatment, demonstrations of injection technique for CCH-aaes, and a review of considerations for the use of CCH-aaes in real-world clinical practice. Results: The practical guidance presented here is based upon real-world experience with CCH-aaes. The discussion includes strategies based on early experience for how to obtain the best results as well as suggestions on how to mitigate bruising. Conclusions: CCH-aaes has been a welcome addition to the armamentarium for the treatment of cellulite. With knowledge of proper patient evaluation and injection technique, thorough patient education, diligent photography, and developing research on bruising mitigation, CCH-aaes shows great promise as an effective and safe modality for the management of cellulite.